A modified lithium manganese iron phosphate positive electrode material and its preparation method and application

Doping LMFP with Nb and coating it with LiNbO3 and Nb2O5 improves conductivity and cycle stability, addressing the limitations of LMFP in lithium-ion batteries.

CN116014122BActive Publication Date: 2024-12-13EVE POWER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211611334.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-14
Publication Date
2024-12-13
Estimated Expiration
2042-12-14

AI Technical Summary

Technical Problem

Lithium manganese iron phosphate (LMFP) positive electrode materials suffer from low electronic conductivity, ion diffusion rate, and poor cycle performance, limiting their industrial application in lithium-ion batteries.

Method used

A modified lithium manganese iron phosphate material is doped with Nb element and coated with LiNbO3 and Nb2O5, enhancing conductivity and stability through a synergistic effect.

Benefits of technology

The modified material exhibits improved rate performance and long cycle life, with LiNbO3 acting as a fast ion conductor and Nb2O5 providing a protective layer, stabilizing the lattice and inhibiting side reactions.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention provides a modified lithium iron manganese phosphate positive electrode material and a preparation method and application thereof. The modified lithium iron manganese phosphate positive electrode material comprises a doped lithium iron manganese phosphate core and a coating layer arranged on the surface of the doped lithium iron manganese phosphate core, the doped lithium iron manganese phosphate core comprises Nb element, the coating layer comprises LiNbO3 and Nb2O5, the modified lithium iron manganese phosphate positive electrode material of the present invention is doped with Nb element, and the surface is double-coated with LiNbO3 and Nb2O5, the coating layer of the modified lithium iron manganese phosphate positive electrode material has good uniformity, consistency and conductivity, and LiNbO3 and Nb2O5 synergistically improve the rate performance and long cycle performance of LMFP electrode materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries and relates to a modified lithium manganese iron phosphate positive electrode material and a preparation method and application thereof. Background Art

[0002] In recent years, the vigorous development of new energy vehicles has driven the rapid growth of demand for lithium-ion power batteries. At present, the cathode materials of lithium-ion power batteries are mainly lithium iron phosphate (LFP) and ternary materials. Among them, LFP has gradually become the preferred choice of energy storage and power battery companies due to its advantages such as high cost performance, high safety and small resource bottleneck. However, it has the problem of low energy density, which has become a key factor restricting the large-scale application of lithium iron phosphate.

[0003] Lithium manganese iron phosphate (LMFP) is a positive electrode material obtained by adding manganese to LFP. Manganese doping can make LMFP have a higher voltage platform (4.1Vvs3.4V), and the energy density of the battery is increased by about 15%. It is a positive electrode material with great application prospects. At present, LMFP positive electrode materials are still in the early stages of industrialization. The main reason is that LMFP has low electronic conductivity and ion diffusion rate, low first coulomb efficiency, and poor cycle performance, which seriously affects its commercial landing. Therefore, how to improve the electronic conductivity, ion transfer rate and cycle stability of LMFP materials is the current technical key. At present, an effective way to solve this technical problem is to perform lattice doping and double-coating integrated modification on the LMFP material.

[0004] CN114335480A provides a preparation method and application of a core-shell carbon-coated doped lithium iron phosphate, wherein the method firstly causes a chelation reaction between an iron source, a transition metal compound and tannic acid, and then the chelate is subjected to a hydrothermal synthesis reaction with a phosphorus source and a lithium source to obtain a tannic acid-coated transition metal ion-doped lithium iron phosphate precursor, and finally the tannic acid is sintered and carbonized under an inert atmosphere to obtain a core-shell carbon-coated doped lithium iron phosphate. The chelation reaction used in the method can inhibit the loss of transition metal ions, and the tannic acid carbonization can inhibit the agglomeration of secondary particles, so that the cathode material obtained can obtain better rate and kinetic performance in application, but the cycle performance is not significantly improved and cannot meet the requirements of power batteries.

[0005] CN113942990A discloses a carbon-coated and ion-doped lithium manganese iron phosphate positive electrode material prepared by co-precipitation reaction. This method overcomes the problems of uneven element distribution, low compaction density and low specific capacity of the lithium manganese iron phosphate positive electrode material, but the material has poor cycle stability. After the assembled button battery is cycled for 80 weeks at a rate of 1C, the capacity decays to 95.8%. Summary of the invention

[0006] The purpose of the present invention is to provide a modified lithium iron manganese phosphate positive electrode material and a preparation method and application thereof. The modified lithium iron manganese phosphate positive electrode material of the present invention is doped with Nb element, and the surface is double-coated with LiNbO3 and Nb2O5. The coating layer of the modified lithium iron manganese phosphate positive electrode material has good uniformity, consistency and conductivity. LiNbO3 and Nb2O5 synergistically improve the rate performance and long cycle performance of the LMFP electrode material.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a modified lithium iron manganese phosphate positive electrode material, comprising a doped lithium iron manganese phosphate core and a coating layer arranged on the surface of the doped lithium iron manganese phosphate core, the doped lithium iron manganese phosphate core comprises Nb element, and the coating layer comprises LiNbO3 and Nb2O5.

[0009] The modified lithium manganese iron phosphate positive electrode material of the present invention is doped with Nb element in the bulk phase, and double-coated with LiNbO3 and Nb2O5 on the surface, wherein Nb has a strong interatomic force after doping, can stabilize the lattice structure, improve the dissolution of manganese, reduce Li / Ni mixing, and improve the lithium ion diffusion coefficient; Nb2O5 has a strong stability within the working voltage range, can effectively inhibit the side reaction between the electrode and the electrolyte and enhance the interface stability, and improve the cycle stability of the LMFP positive electrode material; LiNbO3 can not only serve as a physical barrier to enhance the interface stability, but also serve as a fast ion conductor to promote the rapid conduction of lithium ions.

[0010] Preferably, the chemical formula of the doped lithium manganese iron phosphate core is LiNb a Mn x Fe 1-x PO4, where 0 <a≤0.05,0<x<1。

[0011] Preferably, the coating layer has a thickness of 10 to 50 nm, for example, 10 nm, 20 nm, 30 nm, 40 nm or 50 nm.

[0012] Preferably, the molar mass ratio of LiNbO3 and Nb2O5 in the coating layer is 1:(0.1-0.4), for example: 1:0.1, 1:0.15, 1:0.2, 1:0.25, 1:0.3, 1:0.35 or 1:0.4, etc.

[0013] In a second aspect, the present invention provides a method for preparing the modified lithium manganese iron phosphate positive electrode material as described in the first aspect, the preparation method comprising the following steps:

[0014] (1) mixing a lithium source, a manganese source, an iron source and a phosphorus source with a solvent to obtain a mixed salt solution, mixing the mixed salt solution, a niobium source and a complexing agent, drying and sintering to obtain a sintered material;

[0015] (2) mixing the calcined material obtained in step (1), LiNbO3, and Nb2O5 with an organic solvent and grinding them;

[0016] (3) calcining the material obtained by the grinding treatment in step (2) to obtain the modified lithium manganese iron phosphate positive electrode material.

[0017] The present invention first synthesizes Nb-doped LMFP, then mixes LiNbO3 and Nb2O5 in a certain proportion, and then dry-mixes LMFP with a coating mixture, followed by sintering to obtain a doped and double-coated integrated modified LMFP positive electrode material. The prepared coating layer has good uniformity, consistency and conductivity. The preparation process of the method is simple and controllable, and is easy for large-scale industrial production.

[0018] Preferably, the lithium source in step (1) comprises lithium carbonate and / or lithium dihydrogen phosphate.

[0019] Preferably, the manganese source includes any one of manganese sulfate, manganese carbonate, manganese nitrate, manganese acetate or manganese oxalate, or a combination of at least two thereof.

[0020] Preferably, the iron source comprises iron phosphate and / or iron powder.

[0021] Preferably, the phosphorus source comprises phosphoric acid and / or diammonium phosphate.

[0022] Preferably, the molar ratio of each element in the mixed salt solution is Li:Mn:Fe:P=(1-1.6):x:(1-x):1,0 <x<1。

[0023] Preferably, the niobium source includes any one of niobium oxide, niobium hydroxide, niobium chloride, niobium sulfate, niobium nitrate or niobium acetate, or a combination of at least two thereof.

[0024] Preferably, the complexing agent comprises sodium alginate.

[0025] Preferably, the drying method in step (1) comprises spray drying.

[0026] Preferably, the sintering temperature is 600-900°C, for example, 600°C, 750°C, 800°C, 850°C or 900°C.

[0027] Preferably, the sintering treatment time is 6 to 15 hours, for example: 6 hours, 8 hours, 10 hours, 12 hours or 15 hours.

[0028] Preferably, the atmosphere of the sintering process includes a nitrogen atmosphere.

[0029] Preferably, the organic solvent in step (2) comprises ethanol.

[0030] Preferably, the grinding speed is 500-1000 rpm, for example, 500 rpm, 600 rpm, 700 rpm, 800 rpm, 900 rpm or 1000 rpm.

[0031] Preferably, the grinding treatment time is 0.3 to 1 h, for example, 0.3 h, 0.5 h, 0.6 h, 0.8 h or 1 h.

[0032] Preferably, the mass ratio of the total mass of LiNbO3 and Nb2O5 to the mass of the sintered material is 0.1 to 10:100, for example, 0.1:100, 0.5:100, 1:100, 5:100 or 10:100, and preferably 0.5 to 2:100.

[0033] Preferably, the temperature of the calcination treatment in step (3) is 200-650°C, for example, 200°C, 300°C, 400°C, 500°C or 650°C.

[0034] Preferably, the calcination treatment time is 2 to 15 hours, for example, 2 hours, 5 hours, 8 hours, 10 hours or 15 hours.

[0035] In a third aspect, the present invention provides a positive electrode plate, wherein the positive electrode plate comprises the modified lithium manganese iron phosphate positive electrode material as described in the first aspect.

[0036] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode sheet as described in the third aspect.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] (1) The modified lithium manganese iron phosphate positive electrode material of the present invention is doped with Nb element, and the surface is double-coated with LiNbO3 and Nb2O5. The coating layer of the modified lithium manganese iron phosphate positive electrode material has good uniformity, consistency and conductivity. LiNbO3 and Nb2O5 synergistically improve the rate performance and long cycle performance of the LMFP electrode material.

[0039] (2) Nb 5+ Doping layered transition metal oxide cathode materials can inhibit cation mixing and significantly improve the rate performance and cycle stability of the materials; LiNbO3 coated modified cathode materials, due to their high lithium ion conductivity, can effectively isolate organic electrolytes while ensuring that the rate performance of the materials is not reduced. 5+Doping and / LiNbO3 structure will have a synergistic effect, significantly improving the rate, cycle and safety performance. T-Nb2O5 (T-phase niobium oxide) has a special lithium ion transmission channel and excellent rate performance, comparable to the best solid electrolyte. Currently, T-phase niobium oxide has been used as a high-rate negative electrode material for lithium batteries. Using T-Nb2O5 as a niobium source, in the construction of Nb 5+ While doping / LiNbO3 coating, the excess niobium source (T-Nb2O5) remains on the surface of the material and can continue to serve as a physical protective layer without reducing the rate performance of the material. DETAILED DESCRIPTION

[0040] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0041] Example 1

[0042] This embodiment provides a modified lithium iron manganese phosphate positive electrode material, and the modified lithium iron manganese phosphate positive electrode material is prepared by the following method:

[0043] (1) lithium carbonate, manganese sulfate, iron powder and phosphoric acid were weighed according to the molar ratio of Li:Mn:Fe:P=1.08:0.7:0.3:1, added to deionized water for dispersion and stirring, and then niobium chloride and sodium alginate were added. After stirring at a stirring speed of 1000 rpm for 3 hours, spray drying was performed, and the mixture was placed in a box furnace protected by nitrogen atmosphere, and the temperature was increased to 780°C at a heating rate of 5°C. After keeping the temperature for 10 hours, a calcined material was obtained;

[0044] (2) LiNbO3 and Nb2O5 were added into a high-speed mixer at a ratio of 1:0.25 and mixed at a speed of 800 rpm for 0.5 h to obtain a coated mixture, and then the coated mixture and the calcined material obtained in step (1) were dispersed in an ethanol solvent, stirred and ground, wherein the coating mixture accounted for 1%, the ball milling speed was 600 rpm, and the ball milling time was 2 h;

[0045] (3) Sintering in a nitrogen atmosphere, with a sintering heating rate of 8°C / min, a sintering temperature of 650°C, and a calcination time of 2h, followed by cooling to room temperature in a nitrogen atmosphere to obtain the modified lithium manganese iron phosphate positive electrode material, wherein the coating layer thickness of the modified lithium manganese iron phosphate positive electrode material is 25nm.

[0046] Example 2

[0047] This embodiment provides a modified lithium iron manganese phosphate positive electrode material, and the modified lithium iron manganese phosphate positive electrode material is prepared by the following method:

[0048] (1) lithium carbonate, manganese sulfate, iron powder and phosphoric acid were weighed according to the molar ratio of Li:Mn:Fe:P=1.08:0.7:0.3:1, added to deionized water for dispersion and stirring, and then niobium chloride and sodium alginate were added. After stirring at a stirring speed of 1200 rpm for 3 hours, spray drying was performed, and the mixture was placed in a box furnace protected by nitrogen atmosphere, and the temperature was increased to 790°C at a heating rate of 8°C. After keeping the temperature for 9 hours, a calcined material was obtained;

[0049] (2) LiNbO3 and Nb2O5 were added into a high-speed mixer in a ratio of 1:0.3 and mixed at a speed of 850 rpm for 0.5 h to obtain a coated mixture. The coated mixture and the calcined material obtained in step (1) were then dispersed in an ethanol solvent, stirred and ground, wherein the coating mixture accounted for 1%, the ball milling speed was 600 rpm, and the ball milling time was 2 h;

[0050] (3) Sintering in a nitrogen atmosphere at a heating rate of 8° C. / min, a sintering temperature of 680° C., and a calcination time of 2 h, followed by cooling to room temperature in a nitrogen atmosphere to obtain the modified lithium manganese iron phosphate positive electrode material.

[0051] Example 3

[0052] The only difference between this embodiment and embodiment 1 is that the mass ratio of LiNbO3 and Nb2O5 is 1:0.05, and the other conditions and parameters are exactly the same as those in embodiment 1.

[0053] Example 4

[0054] The only difference between this embodiment and embodiment 1 is that the mass ratio of LiNbO3 and Nb2O5 is 1:0.6, and the other conditions and parameters are exactly the same as those in embodiment 1.

[0055] Comparative Example 1

[0056] The only difference between this comparative example and Example 1 is that the core is not doped with Nb, and the other conditions and parameters are exactly the same as those in the example.

[0057] Comparative Example 2

[0058] The only difference between this comparative example and Example 1 is that LiNbO3 is not added, and other conditions and parameters are exactly the same as those of the example.

[0059] Comparative Example 3

[0060] The only difference between this comparative example and Example 1 is that Nb2O5 is not added, and the other conditions and parameters are exactly the same as those in the example.

[0061] Performance Testing:

[0062] The lithium manganese iron phosphate prepared in Examples 1-4 and Comparative Examples 1-3 was selected as the positive electrode material, and the graphite carbon material was selected as the negative electrode material, and PE / PP polymer material was used as the diaphragm. The core was assembled into a roll by winding or lamination, encapsulated in an aluminum shell or aluminum-plastic film, and injected with a lithium ion electrolyte composed of EC / EMC and LiPF6 to assemble into an aluminum shell or soft-pack lithium ion battery. The discharge rate at 3C and the capacity retention rate after 1000 cycles at 1C at 25°C were tested. The test results are shown in Table 1:

[0063] Table 1

[0064] Discharge rate (%) Cycle capacity retention rate (%) Example 1 96.8 96.9 Example 2 95.0 95.6 Example 3 94.6 95.0 Example 4 93.2 97.2 Comparative Example 1 88.4 90.1 Comparative Example 2 85.0 89.0 Comparative Example 3 96.0 85.0

[0065] By comparing Example 1 with Examples 3-4, it can be seen that in the modified lithium manganese iron phosphate positive electrode material of the present invention, the mass ratio of LiNbO3 and Nb2O5 will affect its performance. When the mass ratio of LiNbO3 and Nb2O5 is controlled at 1:(0.1-0.4), the performance of the obtained positive electrode material is better. If the mass proportion of LiNbO3 is too large, the material stability is poor and the cycle capacity retention rate is low. If the mass proportion of Nb2O5 is too large, the material rate performance is poor.

[0066] By comparing Example 1 with Comparative Example 1, it can be seen that the modified lithium manganese iron phosphate core of the present invention has a strong interatomic force after Nb doping, which can stabilize the lattice structure, improve the dissolution of manganese, reduce Li / Ni mixing, and increase the lithium ion diffusion coefficient.

[0067] From the comparison between Example 1 and Comparative Example 2, it can be seen that LiNbO3 can not only serve as a physical barrier to enhance interface stability, but also serve as a fast ion conductor to promote rapid conduction of lithium ions.

[0068] By comparing Example 1 and Comparative Example 3, it can be seen that Nb2O5 has strong stability within the operating voltage range, can effectively inhibit the side reaction between the electrode and the electrolyte and enhance the interface stability, thereby improving the cycle stability of the LMFP positive electrode material.

[0069] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A modified lithium manganese iron phosphate positive electrode material, characterized in that: The modified lithium iron manganese phosphate positive electrode material comprises a doped lithium iron manganese phosphate core and a coating layer arranged on the surface of the doped lithium iron manganese phosphate core, the doped lithium iron manganese phosphate core comprises Nb element, and the coating layer comprises LiNbO3 and Nb2O5; The mass ratio of LiNbO3 to Nb2O5 in the coating layer is 1:(0.1-0.4).

2. The modified lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The chemical formula of the doped lithium manganese iron phosphate core is LiNb a Mn x Fe 1-x PO4, where 0 <a≤0.05,0<x<1。 3. The modified lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The coating layer has a thickness of 10 to 50 nm.

4. A method for preparing the modified lithium manganese iron phosphate positive electrode material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) mixing a lithium source, a manganese source, an iron source and a phosphorus source with a solvent to obtain a mixed salt solution, mixing the mixed salt solution, a niobium source and a complexing agent, drying and sintering to obtain a sintered material; (2) mixing the calcined material obtained in step (1), LiNbO3, and Nb2O5 with an organic solvent and grinding them; (3) calcining the material obtained by the grinding treatment in step (2) to obtain the modified lithium manganese iron phosphate positive electrode material.

5. The preparation method according to claim 4, characterized in that: The lithium source in step (1) includes lithium carbonate and / or lithium dihydrogen phosphate.

6. The preparation method according to claim 4, characterized in that: The manganese source in step (1) includes any one of manganese sulfate, manganese carbonate, manganese nitrate, manganese acetate or manganese oxalate, or a combination of at least two thereof.

7. The preparation method according to claim 4, characterized in that: The iron source in step (1) includes iron phosphate and / or iron powder.

8. The preparation method according to claim 4, characterized in that: The phosphorus source in step (1) includes phosphoric acid and / or diammonium phosphate.

9. The preparation method according to claim 4, characterized in that: The molar ratio of each element in the mixed salt solution of step (1) is Li:Mn:Fe:P=(1-1.6):x:(1-x):1,0 <x<1。 10. The preparation method according to claim 4, characterized in that: The niobium source in step (1) includes any one of niobium oxide, niobium hydroxide, niobium chloride, niobium sulfate, niobium nitrate or niobium acetate, or a combination of at least two thereof.

11. The preparation method according to claim 4, characterized in that: The complexing agent in step (1) includes sodium alginate.

12. The preparation method according to claim 4, characterized in that: The drying method in step (1) includes spray drying.

13. The preparation method according to claim 4, characterized in that: The sintering temperature in step (1) is 600-900°C.

14. The preparation method according to claim 4, characterized in that: The sintering time in step (1) is 6 to 15 hours.

15. The preparation method according to claim 4, characterized in that: The atmosphere of the sintering treatment in step (1) includes a nitrogen atmosphere.

16. The preparation method according to claim 4, characterized in that: The organic solvent in step (2) includes ethanol.

17. The preparation method according to claim 4, characterized in that: The grinding speed in step (2) is 500-1000 rpm.

18. The preparation method according to claim 4, characterized in that: The grinding time in step (2) is 0.3 to 1 h.

19. The preparation method according to claim 4, characterized in that: In step (2), the total mass ratio of LiNbO3 and Nb2O5 to the mass ratio of the sintered material is 0.1 to 10:

100.

20. The preparation method according to claim 19, characterized in that: The mass ratio of the total mass of LiNbO3 and Nb2O5 to the mass of the sintered material in step (2) is 0.5 to 2:

100.

21. The preparation method according to claim 4, characterized in that: The temperature of the calcination treatment in step (3) is 200-650°C.

22. The preparation method according to claim 4, characterized in that: The calcination time in step (3) is 2 to 15 hours.

23. A positive electrode sheet, characterized in that: The positive electrode plate comprises the modified lithium manganese iron phosphate positive electrode material as described in any one of claims 1-3.

24. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet as claimed in claim 23.